Growth traits and beet weight of tropical sugar beet responses to foliar application of boron - Bithy, Shritinnahar; Mahapatra, Chandan Kumar; Sarkar, Shubroto Kumar; Hossain, Md Sohrab; Sarkar, Md Abdur Rahman; Paul, Swapan Kumar (Research in Agriculture Livestock and Fisheries, 2021)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to assess the response of foliar application of boron on growth and beet weight. The experiment consisted of foliar application of boron at four concentrations viz. 0, 50, 100 and 150 ppm, and frequency of application thrice viz. once at 40 days after emergence (DAE), twice at 40 and 65 DAE and thrice at 40, 65 and 90 DAE. The experiment was laid out in a randomized complete block design with three replications. Growth traits and average beet weight were significantly influenced by boron concentration and frequency of application. At later stage of growth (at 140 days after sowing) the tallest plant, number of leaves/plants, shoot dry weight, root dry weight and root length were recorded in 150 ppm boron with three times foliar application at 40, 65 and 90 DAE. The highest average beet weight (1.04 kg/beet) was recorded in 150 ppm boron with foliar application thrice at 40, 65 and 90 DAE followed by 100 ppm boron with foliar application at 40, 65 and 90 DAE while the lowest one 0.28 kg/beet was found in control. So, from the result it can be concluded that 150 ppm boron with foliar application at 40, 65 and 90 DAE seems to be promising in terms of growth attributes and average beet weight/plant of tropical sugar beet. Res. Agric., Livest. Fish.8(2): 181-191, August 2021